(3cJGH GdSdhGf GdeWGYs - (3CHh YHO Gddg eMeO Hf eMeO Hf CHi GdbGSe Hf Ydj GdbQTi GdeYQha HGHf XaQ,J (B565 (3g` s
(3ChdgG (B:s
(3aGdMeO ddg LGYd GdUHQ ddfLGM VejfkG hGdeMHhH ai GdecQhg cejfkG GdSdhGfI GdChdi ai GdJahjV s
(3BNQgG (B:s
(3hGSJcai aSGO GdNWC hcSGO GdUhGH hCJhH Edjg QGLjkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B230 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B998s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs